STUDENTS' CRITICAL THINKING SKILLS IN LEARNING PHYSICAL AND CHEMICAL CHANGES THROUGH HYBDRID LEARNING - Eneng Rahmayanti; Sumar Hendayana; Riandi Riandi (Universitas Muhammadiyah Semarang, 2021)
Online learning in Pandemic COVID-19 requires teachers to be more creative and innovative. Among of them, in dealing with the implementation of science experiment which is needed to build critical thinking skills of students through real phenomena that they do and observe by themselves. Students are possible to do a simple science experiment of physical and chemical changes utilize simple apparatuses and available local materials at home. This study aims to analysis student‟s critical thinking in combined online learning (practice assignments, and online discussions) and hands on activities of physical and chemical change at home. Based on the results of descriptive research of student‟s dialogue analysis during the learning process (online session), it was found that this learning is able to involve all students in critical thinking activities according to Ennis (1985) indicators. In the introduction session (main room) it was found one indicator of critical thinking skills activity with a percentage of 47%. In 1 session, group discussion activities (breakout room 1), it was found 4 critical thinking indicators with a percentage of 80%. In class discussion activities (main room), it was found 6 critical thinking indicators with a percentage 100%. In session 2 group discussion activities (breakout room 2), it was found 3 critical thinking indicators with a percentage of 40%. And In the closing session, it was not found critical thinking activity. From the results of this study, it can be said that the combination of online and hands on methods might be an alternative to the implementation of study at home to build students' critical thinking, within the allocation of learning time. Keywords: critical thinking skills, physical and chemical changes, hybrid learning.